An Identification of Language Uses in Case of Criminal Threatening in Sampang, Madura: A Forensic Linguistic Study - Mashud; Sailal Arimi (Universitas Islam Negeri Palopo, 2025)
Forensic linguistics research in Indonesia has experienced significant development. Based on 200 articles from Google Scholar and processed using VosViewer, forensic linguistics research examines many cases of insult, defamation, good, hearing, regulation, and blasphemy. So, the research analyzes the threats in Sampang Madura. This research aims to describe the linguistic features in the case of threatening criminal offense in Sampang Madura. The research used a descriptive qualitative method. Data collection techniques using documentation techniques. The data source in this research is obtained from the official website of the Supreme Court (https://putusan3.mahkamahagung.go.id/direktori.html). The data in the research is the Decision of Sampang District Court Number 126/Pid.B/2014/PN Spg. The researcher used a note-taking technique to collect language containing threatening elements. To analyze the data, the researcher used the theoretical approaches of pragmatics, sociolinguistics, and systemics functional. The results showed that the use of language in the case of criminal acts of threatening in Sampang Madura fulfills the elements of threatening as stated in Article 89 of the Criminal Law Code (KHUP). The perpetrator has violated four principles of cooperation, namely, maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner. In addition, the situation of the conversation is informal because the perpetrator and the victim use an informal language style. The cultural register is found in the word “carok” which shows that the perpetrator is an ethnic Madurese himself. Based on the metafunctional meaning, the perpetrator deliberately intends to threaten the victim because there is a mental process (desire) to finish off the victim's life. in terms of interpersonal language, the perpetrator does use the utterance “Kamu ini apa mau carok ya sama saya? (Do you want to carok with me?)” in interrogative mode; however, in terms of modality, the utterance is declarative.